Impact of nitrogen fertilization on Mexican rice borer (Lepidoptera: Crambidae) injury and yield in bioenergy sorghum. (June 2016) - VanWeelden, M.T.; Wilson, B.E.; Beuzelin, J.M.; Reagan, T.E.; Way, M.O.
Abstract: The Mexican rice borer, Eoreuma loftini (Dyar) (Lepidoptera: Crambidae), is a serious pest of sugarcane ( Saccharum spp.), sorghum ( Sorghum bicolor (L.) Moench), corn ( Zea mays L.), rice ( Oryza sativa L.), and related graminaceous bioenergy crops. A two-year field study was conducted in Jefferson County, TX to examine the impact of nitrogen (N) fertilization on E. loftini infestations and subsequent yields in cultivars of high-biomass and sweet sorghum. In 2013, percentage of bored internodes and number of adult emergence holes per stalk increased with higher N rates; however, only the percentage of bored internodes was impacted by N in 2014. Yields from both years indicated that N rate was positively associated with increases in stalk weight and ethanol productivity, but not sucrose concentration. Because higher N rates were associated with increased yields despite having greater levels of E. loftini injury, our data suggest that increases in yield from additional N outweigh decreases from additional E. loftini injury. Fertilization rates maintained between the recommended 45 and 90 kg N/ha minimize risks of negative area-wide impacts from increased production of E. loftini adults, while still allowing for optimum yields. Highlights: The Mexican rice borer, Eoreuma loftini, is a threat to bioenergy sorghum production. E. loftini injury was greater at higher nitrogen rates. Added nitrogen likely masked yield losses attributed E. loftini feeding. Nitrogen rates between 45 and 90 kg N/ha can minimize production of E. loftini adults.